2012
DOI: 10.1111/j.1365-2966.2012.21020.x
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy And Mass Assembly (GAMA): estimating galaxy group masses via caustic analysis

Abstract: We have generated complementary halo mass estimates for all the groups in the Galaxy And Mass Assembly Galaxy Group Catalogue (GAMA G3Cv1) using a modified caustic mass estimation algorithm, originally developed by Diaferio & Geller. We calibrate the algorithm by applying it on a series of nine GAMA mock galaxy light cones and investigate the effects of using different definitions for group centre and size. We select the set of parameters that provide median‐unbiased mass estimates when tested on mocks, and ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Our isolated galaxies are therefore considered to be isolated down to GAMA's detection limit of mr = 19.8 mag. The accuracy of these group and pair classifications has been indepently verified (Alpaslan et al 2012), and benefits from GAMA's high target density and spectroscopic completeness, ensuring that our isolation criteria for our sample is very robust. By excluding such paired and grouped galaxies, one can study the stellar mass growth of spiral galaxies whose stellar populations and star formation rates are not affected by processes that typically affect star formation in groups and pairs (e.g Ellison et al 2008;Robotham et al 2013;Davies et al 2015).…”
Section: Spiral Galaxy Selectionmentioning
confidence: 83%
“…Our isolated galaxies are therefore considered to be isolated down to GAMA's detection limit of mr = 19.8 mag. The accuracy of these group and pair classifications has been indepently verified (Alpaslan et al 2012), and benefits from GAMA's high target density and spectroscopic completeness, ensuring that our isolation criteria for our sample is very robust. By excluding such paired and grouped galaxies, one can study the stellar mass growth of spiral galaxies whose stellar populations and star formation rates are not affected by processes that typically affect star formation in groups and pairs (e.g Ellison et al 2008;Robotham et al 2013;Davies et al 2015).…”
Section: Spiral Galaxy Selectionmentioning
confidence: 83%
“…The application of the caustic technique (e.g., Alpaslan et al 2012;Serra & Diaferio 2013) is shown in panels (c & g) of Figure 8 for two rescale parameters, q = 25 (cyan lines) and q = 35 (pink lines). Although this technique is quite successful when applied to the cluster outskirts, it misses some of the true members located within the core, which are the most important galaxies affecting the dynamics of the clusters.…”
Section: A Comparison Of Membershipmentioning
confidence: 99%
“…Cluver et al (2014) obtained mid-infrared photometry for GAMA galaxies from reprocessed WISE data. Finally, the environment of GAMA galaxies was characterized by Brough et al (2013) using galaxy number surface density, while presented the GAMA Galaxy Group Catalogue (G 3 C; see also Alpaslan et al 2012). The above have been used, inter alia, to derive the broad-band (Loveday et al 2012(Loveday et al , 2015 and Hα (Gunawardhana et al 2013) luminosity and stellar mass (Baldry et al 2012;Gunawardhana et al 2015) functions, to consider the luminosity and stellar mass functions split by Hubble type (Kelvin et al 2014a,b) and in different environments (McNaught-Roberts et al 2014;Eardley et al 2015), to determine the effect of mergers on the stellar mass function , to study variations and dependences of the galaxy initial mass function (Gunawardhana et al 2011) and of the star formation rate (SFR; Wijesinghe et al 2012), and to investigate satellite galaxies (Prescott et al 2011;Schneider et al 2013), the effect of the local environment on L galaxies (Robotham et al 2013), the relations between stellar mass, metallicity and (specific) SFR (Foster et al 2012;Bauer et al 2013;Lara-López et al 2013), and the cosmic spectral energy distribution (SED; Driver et al 2012).…”
Section: Introductionmentioning
confidence: 99%